THE ART OF PERSONAL IMAGE MANAGEMENT WITH DR. WENDY LEE - Lee, Cheng May; Abdullah Adnan, Mohamed (UMPSA, 2025)
PEKAN, 28 April 2025 - It was a remarkable day, as we had the privilege of attending a lecture on personal image management by Dr. Wendy Lee, the founder of Chapter One Asia, and also the Adjunct Professor CEO@Faculty for Centre for Modern Languages UMPSA. The session, divided into four insightful segments, profoundly enriched our understanding.